The Stellar Initial Mass Function of Early Dark Matter–free Gas Objects - William Lake; Michael Y. Grudić; Smadar Naoz; Naoki Yoshida; Claire E. Williams; Blakesley Burkhart; Federico Marinacci; Mark Vogelsberger; Avi Chen (The Astrophysical Journal Letters)
Among the remarkable strides made by JWST is the discovery of the earliest star clusters found to date. These have been proposed as early progenitors of globular clusters, which are known to come from the early stages of star formation in the Universe. This is an exciting development in modern astronomy, as it offers an opportunity to connect theoretical models of globular cluster formation to actual observations of these high-redshift structures. In this work, we aim to develop observational signatures of a star cluster formation route known as supersonically induced gas objects, which are dark matter–less gas clouds in the early Universe proposed as a potential origin of some globular clusters. For the first time, we follow the star formation process of these early Universe objects using high-resolution hydrodynamical simulations, including mechanical feedback. Our results suggest that the first dark matter–less star clusters are top heavy, meaning that they have a flatter initial mass function slope compared to very young low-metallicity star clusters in the local Universe, and they also have extremely high stellar mass surface densities compared to their local counterparts.